Promoting workplace-based training to fight youth unemployment in three EU countries: Different strategies, different results? - Marques, Paulo; Hörisch, Felix (International journal of social welfare, 2019)
During the economic crisis, youth unemployment grew exponentially in many European countries. It was argued that countries with a high level of firm involvement in the provision of initial vocational training were better equipped to address this problem. Boosting workplace-based training was therefore seen as the right strategy to tackle unemployment. Using Denmark, Spain and the UK as case studies, this article analyses how countries with different skill formation systems have improved this type of training. While the UK reinforced the voluntaristic character of its training regime, Denmark improved the quality of its vocational education, and Spain made reforms to the training and apprenticeship contract. Interestingly, the countries achieved different results. To explain this divergence, it is argued that while the reforms made in the UK and Denmark were compatible with the national institutions and coordination mechanisms, this was not the case in Spain, where reforms were implemented in a non-complementary way. Key Practitioner Message: After the economic crisis it was argued that countries with a high level of firm involvement in the provision of initial VET were better equipped to fight youth unemployment. The study analysed how countries with different skill formation systems improved this type of training and assessed their relative success. The article shows that when implementing reforms policy makers must take into account the institutions and mechanisms of coordination that prevail in each country. Otherwise, reforms may be unsuccessful.
Gesehen am 11.10.2019